Status Perkawinan Beda Agama Tinjaun Maqasit Al-Syariah (Studi Putusan 916/Pdt.P/2022/PN.Sby.) - Sarna, Sarnawiah; Aisiyiah, Wirani (IAIN Parepare, 2025)
Marriage is not a purely civil relationship like other civil matters, so religion is the basis for determining whether a marriage is legal. Therefore, in the marital relationship, it is viewed from a pluralistic, social, cultural, racial, linguistic, ethnic and religious perspective.It plays a very important role in building harmony and happiness in the home. In essence, religion neutralizes social, cultural, ethnic, national, and racial stratification differences. In addition to protecting religion (hifz al-Dîn), the ban on interreligious marriage also helps protect descendants (hifz al-Nasl). When we discuss marriage, we discuss not only the interests of both parties (husband and wife), but also the interests of the family and society. Marriage is strictly religious and regulated by law to protect the rights of both parties and their descendants. When a judge examines and interprets marriage law, he neither rules nor permits interfaith marriages in favor of the Umma, either in this life or in the hereafter.